Evaluating the Struggles with International Students and Local Community Participation - Kusek, Weronika A. (Journal of International Students, 2015)
International students are not only important for universities, but even more so to the host communities, towns and regions where higher education institutions are located. This pilot study looked at a public university located in a small college town in Ohio. The study explored the relationship between international students and the local community. Data for this study was collected through questionnaires and conversations with international students from seven different countries, and complemented by participant observations. The outcomes of this study suggest that international students at the subject university feel a low level of engagement with the local community. Student questionnaires and conversations indicated that their daily schedules in the United States contained fewer activities and social interactions than in their home towns. The study explored potential reasons for this difference in daily routines and community engagement, as expressed by interviewed students.